Prépositions, adverbes et conjonctions en anglais : pour une redéfinition des classes lexicales - Romain Delhem (Anglophonia)
Traditional grammar describes prepositions as invariable words whose function is to introduce a nominal complement and link it to another word. This definition is challenged by the diversity in the complementation of prepositions, which paves the way for a redefinition of the limits of the category. It is shown that word classes are primarily a tool to make grammatical description easier and not an objective reality. A unified analysis is put forward for after, before and since in English, which are usually split into several classes only because of their complementation. By analogy, it is shown that some units traditionally classified as adverbs and some subordinating conjunctions can be grouped with prepositions inside the same category. This takes into consideration the similarities they exhibit in their syntactic behavior and their meaning.